Improved GNSS Positioning Schemes in Urban Canyon Environments - Jiaqi Li; Seung-Hoon Hwang (IEEE Access)
Accurate positioning in urban canyon environments poses significant challenges owing to signal obstructions, multipath effects, and limited satellite visibility. This paper evaluates the performance of standalone Global Navigation Satellite System (GNSS) positioning in urban canyon environments over three scenarios such as pedestrian, vehicle, and uncrewed aerial vehicle (UAV) for various altitudes and speeds. To improve the performance of the standalone GNSS in the urban canyon conditions, two hybrid positioning solutions such as GNSS with the Quasi-Zenith Satellite System (QZSS) and GNSS with 5G are proposed and their performances are investigated. Through extensive simulations, it is shown that higher speeds and lower receiver altitudes result in higher positioning errors for the standalone GNSS positioning. Additionally, in the UAV scenario, the hybrid solution with GNSS and QZSS demonstrates robust performance with 0% positioning failures and low positioning errors. Meanwhile, in the pedestrian and vehicle scenarios where satellite visibility is severely restricted, the hybrid solution with GNSS and 5G outperforms the hybrid solution with GNSS and QZSS, resulting in reduced positioning errors owing to the superior 5G terrestrial infrastructure.